Effect of Betel leaf extract on the control of stem-end rot disease and overall quality retention of Papaya (Carica papaya L.) during cold storage - Shiraz, Fathumma Rizana (2019)
Postharvest losses of papaya due to fungal diseases is one of the major problem in fruit industry in Malaysia and worldwide. Stem-end rot an important postharvest fungal disease in papaya fruit is caused by Lasiodiplodia theobromae (synonym Botryodiplodia theobromae) This pathogen is a causative agent for the stem-end rot diseases in many other fruits such as Mango, Rambutan, Avocado, Annona and Citrus fruits. No specific control measures have been developed for this disease however, field sprays with systemic and contact fungicides could reduce field inoculum levels and reduce disease incidence. Moreover, due to developed resistance in pathogen and health concerns, there is a great demand to find alternatives to synthetic fungicides.